Contemporary marketing communication in Web 2.0 environment. The potential of viral marketing and social media in a common building of a consumer value - Walewska, Agnieszka Maria (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
In era of information technology the customer has always been the starting point. But this principle gradually becomes outdated with the increasing awareness of the potential of his ideas and social values. Therefore, the main task of today's marketers are not only building relationships with consumers. The more important is to respond to social problems, emotional and spiritual issues and stimulate a consumer activity. In this article will be characterized marketing 3.0 concept, including cultural marketing which is a response to the emotional needs of stakeholders. Moreover, it will be presented a subject of viral and non-standard potential use of social media – a fundamental tool for participation in the creation of value according to the concept of marketing 3.0.